Uncovering Patterns in Dissident Interactions Among Late Medieval German Waldensians Using Social Network Analysis - Välimäki, Reima; Zbíral, David (Arc Humanities Press, 2026)
We use social network analysis to provide a comprehensive overview of the suspects, their social relations, kinship ties, and dissident interactions in the extant protocols from the Stettin inquisition against Waldensians in 1392-4. We provide a general description of the Waldensians appearing in the Stettin records: their places of residence, occupation, and age. We then proceed to consider the insights gained from network analysis. We explore whether the Waldensians interrogated in Stettin formed one connected component, or more components isolated from one another. We also compare the network positions of religious specialists (i.e. Brethren) vs. those of supporters (i.e. local Waldensians). Finally, we analyse the degree to which Brandenburg-Pomeranian Waldensianism was a local and familial phenomenon. In terms of network analysis, this means analysing how far different kinds of social closeness (kinship ties, same gender, and same place of residence) underpinned dissident interactions. Overall, the study provides an important contribution to historical network research, showing the potential of social network analysis to decide controversial questions in medieval studies. Through our analysis of homophily, we also stress that network analysis is not about centralities alone
Social Network Analysis and Medieval History